2018
DOI: 10.1016/j.joca.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive T1ρ mapping of the human cartilage response to loading and unloading

Abstract: Serial T1ρ-mapping reveals distinct and complex zonal and regional changes in articular cartilage as a function of loading and unloading. Thereby, longitudinal adaptive processes in hyaline cartilage become evident, which may be used for the tissue's non-invasive functional characterization by T1ρ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Souza et al found significant decreases in T1r in the tibial cartilage only, while changes in femoral cartilage were discrepant 5,7 . Hamada et al reported decreases in T1r 13 , while our group found consistent increases 8,14 . Although these studies differed in design, loading protocol, tissue source and reference standard, cartilage functionality has been related to tissue degeneration.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…Souza et al found significant decreases in T1r in the tibial cartilage only, while changes in femoral cartilage were discrepant 5,7 . Hamada et al reported decreases in T1r 13 , while our group found consistent increases 8,14 . Although these studies differed in design, loading protocol, tissue source and reference standard, cartilage functionality has been related to tissue degeneration.…”
Section: Introductionsupporting
confidence: 71%
“…Previous studies focusing on loading-induced changes in T1r reported inconsistent (and partially contradictory) results, i.e., increases 8,36 and decreases 7,13 . These discrepancies are most likely due to differences in species, study designs, loading and imaging protocols and segmentation techniques.…”
Section: Tissue Functionality In Degenerative Tissuementioning
confidence: 89%
See 2 more Smart Citations
“…7.0 T or 9.4 T) would have provided better signal-to-noise ratio, such scanners have not (yet) seen widespread clinical application and relaxation times are different from those at 3.0 T 54 . We deliberately chose sequence parameters similar to those in earlier studies [55][56][57][58][59] to render generalizability and transferability of the findings less related to actual sequence parameter settings.…”
Section: Discussionmentioning
confidence: 99%